KOMUNIKASI INTERPERSONAL PERAWAT DENGAN KEPUASAN PASIEN DI RUANG RAWAT BOUGENVIL RSUD TAMAN HUSADA BONTANG - Surya Wijaya; Edi Sukamto; Wiyadi (Jurnal Cakrawala Ilmiah, 2023)
Introduction : Patient satisfaction is an indicator of the success of health services which is influenced by nurses' interpersonal communication in providing nursing actions to patients. Nurses' interpersonal communication can influence the quality of nursing services provided to patients, and can have an impact on patient satisfaction. This study aims to determine the relationship between nurses' interpersonal communication and patient satisfaction in the Bougenvil inpatient room at Taman Husada Bontang Regional Hospital. Method: The method in this research is descriptive correlational with a cross sectional approach. The population in this study were 185 inpatients in the Bougainvillea Room at Taman Husada Bontang Regional Hospital with a total sample of 127 respondents using non-probability sampling methods and consecutive sampling techniques. Data analysis was carried out univariate and bivariate using the Chi-Square test. Research results : There were 69 nurses with good communication (54.3%) and 58 nurses with poor communication (45.7%). Meanwhile, 74 patients were satisfied (58.3) and 53 patients were dissatisfied (41.7). The Chi Square test results obtained p value = 0.008, so the p value is smaller than alpha 0.05, so Ho is rejected. Conclusion : That there is a relationship between nurses' interpersonal communication and patient satisfaction in the Bougenvil inpatient room at Taman Husada Bontang Regional Hospital.